PFOA and its substitutes disrupt fatty acid metabolism and impair erythrocyte homeostasis in zebrafish - Yuanyuan Wu; Weiqiang Sun; Xiyue Liu; Zhonghua Fan; Lin Cheng; Ying Yang; Li Wang; Hui Liu (Ecotoxicology and Environmental Safety)
The accumulation of perfluorooctanoic acid (PFOA) and its substitutes hexafluoropropylene oxide dimer acid (HFPO-DA, trade name Gen-X) and hexafluoropropylene trimer acid (HFPO-TA), which are widely used synthetic chemicals, may pose significant health risks across species. This study systematically investigated the multi-dimensional effects of PFOA and its substitutes on fatty acid metabolic processes and erythrocyte survival through bioinformatic and metabolomics analysis, complemented by a variety of zebrafish exposure experiments, including Oil Red O staining (ORO staining), Nile red staining (NR staining), 1,3-bis(diphenylphosphino)propane (DPPP) and reactive oxygen species (ROS), as well as inflammation, apoptosis and gene expression assays. PFOA and its substitutes significantly disrupted fatty acid oxidation degradation and synthesis, by interfering with the peroxisome proliferator-activated receptor α (PPARα) signaling pathway, leading to lipid accumulation in zebrafish. In addition, PFOA and HFPO-TA reduced the number of erythrocytes in zebrafish through excessive generation of ROS and abnormal activation of the tp53 gene. Gene expression analysis further confirmed that the expression of genes related to fatty acid metabolism, inflammation and apoptosis regulated by PPARα and its target genes were significantly upregulated. This study revealed that PFOA and its substitutes exert multi-dimensional effects on fatty acid metabolism and erythrocyte survival in zebrafish through the activation of PPARα, providing new perspectives for understanding the toxicity mechanisms of per- and polyfluoroalkyl substances (PFAS)